A horizon scan of biological conservation issues for 2025 - Sutherland, William J. (2025)
We discuss the outcomes of our 16th horizon scan of issues that are novel or represent a considerable step-change and have the potential to substantially affect conservation of biological diversity in the coming decade. From an initial 96 topics, our international panel of 32 scientists and practitioners prioritised 15 issues. Technological advances are prominent, including metal and non-metal organic frameworks, deriving rare earth elements from macroalgae, synthetic gene drives in plants, and low-emission cement. We include new insights into accelerated impacts of changes to Antarctic ice masses and air and water quality. We hope that anticipating and mitigating negative impacts, and making best use of new opportunities related to these issues, will contribute to better outcomes for biological diversity.